Peronistas en transición. El proyecto político ideológico en la revista Unidos (1983-1991) - Martina Garategaray (Nuevo mundo - Mundos Nuevos, 2010)
The transition towards democracy in Argentina did not only bring back the political parties to scene, those which were banned during the military dictatorship, but also allowed the rise of political and cultural magazines as means of debate. Amongst them we can name “Unidos” magazine. Unidos, directed by Carlos “Chacho” Alvarez, was published by a group of peronist activists who sought to place Peronism in the new democratic context during May 1983 and August 1991. In this article we will explore the political and ideological project proposed by Unidos. This project was tensed by the proper ups and downs of the Justicialist movement itself, which was signed by the death of Peron and the electoral defeat against the Radical party candidate, Raúl Alfonsín, in October 1983, and its members’ expectations. In this sense we will rebuilt the political bets and ideological definitions of both the politicians and intellectuals merged in this publication. This was a journey containing ruptures and abandonments that brought the “Unidos” to become Peronists in search of new political identities as references, creating new political constitution modes.